Kinerja Pasokan Batubara pada Pembangkit Listrik Tenaga Uap Suralaya - Ahmad Sutrisno; Suharto Abdul Majid; David Lasse (Institut Transportasi dan Logistik Trisakti, 2019)
The purpose of the research to know the effect of ship breasting methods and loading and unloading effectiveness on coal supply performance at PLTU UP Suralaya. The research used survey method. The sample is 118 ship crews who were taken randomly. Data analysis used in this study was descriptive statistics and inferential statistics of path analysis. The results of the research show: there is a positive and significant direct effect of ship breasting methods on coal supply performance; there is a positive and significant direct effect of loading and unloading effectiveness on coal supply performance; there is a positive and significant direct effect of ship breasting methods on loading and unloading effectiveness; and there is a positive and significant indirect effect of ship breasting methods on coal supply performance mediated by loading and unloading effectiveness. The conclusion of the research is that there is a positive and significant effect of ship breasting methods on coal supply performance mediated by loading and unloading effectiveness, so that coal supply performance can be improved through ship breasting methods loading and unloading effectiveness.